PENERAPAN PENGGUNAAN CCTV ( CLOSED CIRCUIT TELEVISIO ) SEBAGAI ALAT BUKTI DI PERSIDANGAN PERKARA PIDANA - Bambang Sukarjono; Angga Pramodya Pradhana; Bella Dwi Sukmaningrum (Universitas Merdeka Madiun, 2023)
This study aims to determine the use of CCTV as evidence in proving criminal cases and proof according to Article 184 of the Criminal Procedure Code and Law Number 19 of 2016 concerning Electronic Information and Transactions. The method used is normative juridical. Where in thisThis study usesin the form of Legislation, Books, and Journals that discuss evidence regarding Electronic Information and Transactions. The results of this study indicate that the position of CCTV as evidence against the perpetrators of criminal acts and the application of the use of CCTV according to KUHAP Article 184, which states that in valid evidence there are witness teismony, expert testimony, letters, instructions, and testimony of the defendant, and is reinforced by the Electronic Information and Transactions Law Number 19 of 2016 in Article 5 paragraph 1, namely that the existence of Electronic Information and / or Electranduments is binding and recognized as valid evidence to provide legal certainty for the Implementation of Electronic Systems and Electronic Transactions, especially in evidence and matters relating to legal acts carried out through Electronic Systems.